Molecular mechanisms of libido influencing semen quality in geese through the hypothalamic-pituitary-testicular-external genitalia axis - Zhiyu He; Tanze Liu; Xiaoyong He; Yang Song; Guibi Li; Xiaopeng Li; Qingyuan Ouyang; Shenqiang Hu; Hua He; Liang Li; Hehe Liu; Jiwen Wang (Poultry Science)
Libido plays a crucial role in influencing semen quality, yet the underlying regulatory mechanisms remain unclear. As a central axis in male goose reproduction, the hypothalamic-pituitary-testicular-external genitalia (HPTE) axis may contribute to the regulation of this process. In this study, we established a rating scale for goose libido based on average number of massages to erection (ANM) and the erection type, and evaluated semen quality across the entire flock. Correlation analyses showed that ANM was negatively correlated with sperm concentration (SC), acrosome integrity (AI), and semen quality factor (SQF), while positively correlated with morphological abnormal sperm (MAS) (P < 0.01). A comparison of semen quality and testicular histology between high libido (HG) and low libido (LG) groups showed that SC and SQF were significantly higher and MAS was lower in HG (P < 0.05). The lumen diameter of seminiferous tubules (LD) (P < 0.01) and the number of Sertoli cells (Sc) (P < 0.05) were also significantly greater in HG. Further, the number of spermatogonia (Sg) was significantly (P < 0.01) lower, and spermatocyte (Sp) and elongated spermatid (Se) were significantly higher in HG (P < 0.05). Through transcriptome sequencing (RNA-seq), we identified 98, 163, 2,474 and 400 differentially expressed genes (DEGs) in the hypothalamus, pituitary, testis and external genitalia, respectively. Gene Ontology (GO) analysis indicated that the term ''male gonad development'' was significantly enriched in the hypothalamus. Here, the expression of LHX9 was positively correlated with ANM, and negatively correlated with SC and SQF (P < 0.05). Additionally, WNT4 was positively correlated with ANM and MAS (P < 0.01), and negatively correlated with SC (P < 0.05), suggesting that LHX9 and WNT4 might serve as key upstream regulatory genes. Further analysis through Weighted Gene Co-Expression Network Analysis (WGCNA) showed that the yellow module (R = 0.89, P = 7e-09) was strongly associated with testicular development, with genes predominantly involved in male reproductive process. Based on these findings, we screened genes significantly correlated with LHX9 and WNT4 from the yellow module (|Cor |≥0.6, P < 0.05). These genes were significantly enriched in 8 pathways, primarily associated with metabolic processes, including drug metabolism - other enzymes, metabolism of xenobiotics by cytochrome P450, metabolic pathways, pyrimidine metabolism, glycerolipid metabolism, and riboflavin metabolism. Using the Maximal Clique Centrality (MCC) algorithm in the CytoHubba plug-in, SYCP3, DDX4, STRA8, AMH, MEIOB, CDT1, BCL2, PRIM1, and DLGAP5 were identified as hub genes. In conclusion, within the HPTE axis, libido might influence metabolism-related signaling pathways (mainly involving genes such as SYCP3, DDX4, STRA8, AMH, MEIOB, CDT1, BCL2, PRIM1, and DLGAP5) through LHX9 and WNT4 to regulate the development of the seminiferous tubules and germ cell number, ultimately affecting SC and MAS in geese. These findings offer practical insights into libido rating and shed light on the mechanisms by which libido regulates semen quality, potentially aiding in the improvement of goose breeding capacity.